2013
DOI: 10.1590/s0102-67202013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Ligadura da veia porta associada à bipartição do fígado para hepatectomia em dois estágios (ALPPS): experiência brasileira

Abstract: -Background -Postoperative liver failure consequent to insufficiency of remnant liver is a feared complication in patients who underwent extensive liver resections. To induce rapid and significant hepatic hypertrophy, associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) has been recently developed for patients which tumor is previously considered unresectable. Aim -To present the Brazilian experience with ALPPS approach. Method -Were analyzed 39 patients who underwent hepatic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Schnitzbauer et al (5) indicated that a two-staged hepatectomy was performed for the first time in a patient with hilar cholangiocarcinoma in 2007 and that associating liver partition and portal vein ligation for staged hepatectomy (ALPPS), a surgical approach for liver cancer with excessive tissue resection, was first described in 2012. However, ALPPS surgery has several limitations, including a large wound surface, incomplete drainage and high mortality rates (5,6). Acute liver and renal failure and infectious complications have been identified as predominant causes for mortality (6).…”
Section: Introductionmentioning
confidence: 99%
“…Schnitzbauer et al (5) indicated that a two-staged hepatectomy was performed for the first time in a patient with hilar cholangiocarcinoma in 2007 and that associating liver partition and portal vein ligation for staged hepatectomy (ALPPS), a surgical approach for liver cancer with excessive tissue resection, was first described in 2012. However, ALPPS surgery has several limitations, including a large wound surface, incomplete drainage and high mortality rates (5,6). Acute liver and renal failure and infectious complications have been identified as predominant causes for mortality (6).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure is consisted of two-staged hepatectomy by which rapid significant hypertrophy of the remnant is induced by transecting the parenchyma while there is not enough time for the development of collateral formation. [10111213141516] The technique is relied on portal vein ligation and in situ splitting through parenchyma so that the two parts are just connected through hilar structures in the first step. Partitioning will be completed after an interval of 7 days if FLR hypertrophy is satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Partitioning will be completed after an interval of 7 days if FLR hypertrophy is satisfactory. [1316] There are promising results on remnant growth rate by ALPPS procedure in literature. [1718] But the reason that the technique is not approved yet is lack of being evaluated technically in early development phase till now.…”
Section: Discussionmentioning
confidence: 99%
“…It should be kept in mind that ALPPS is an “extrema ratio” procedure to be proposed after careful, multidisciplinary patient selection[6,23,24]. Morbidity and mortality amount up to 14% and 6.6% in experienced centers applying strict selection criteria[10,25-27].…”
Section: Alpss: Indications and Techniquementioning
confidence: 99%
“…FLR volume should be calculated by excluding major vessels and FLLs, in order to obtain a reasonable estimate of final viable liver tissue supporting liver function. FLR should be no lower than 25%-30% of preoperative liver volume in patients with normal liver function, and no lower than 40% in patients with underlying chronic liver disease or liver dysfunction (including the effects of chemotherapy)[7,23,50-52]. Many dedicated liver volumetry software are currently available, most times implemented in the picture archive and communication systems used for routine image analysis.…”
Section: Role For Imagingmentioning
confidence: 99%